The Role of Foreign Tourists in Economic Growth: Evidence from Indonesia - Azizurrohman, Muhammad; Hartarto, Romi Bhakti; Lin, Yih-Ming; Nahar, Faiza Husnayeni (Jurnal Ekonomi & Studi Pembangunan, 2021)
Foreign tourism is indicated as one of the important instruments to encourage economic growth in several countries, including Indonesia. However, some studies only focus on the influence of tourist arrivals. Thus, the main objective of this study is to take a deeper look at the contribution of foreign tourism indicators to economic growth in Indonesia. Using panel data analysis from 33 countries between 2006 and 2016, this study applies three models: Pooled Least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (FEM). Based on the fixed-effect model, this study reveals that foreign tourist arrivals have a significant and positive effect on economic growth. However, other tourism indicators such as length of stay and expenditure of foreign tourists appear to have no contribution to economic growth. From these findings, it can be implied that the Indonesian government should not only attract more tourists to come but also design strategies to encourage tourists to spend more money and stay longer. This study also finds that depreciation of Indonesian currency and visa-free policies have a significant contribution to higher economic growth.